2022
DOI: 10.3390/genes13040642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dicationic Imidazolium-Based Ionic Liquid Coatings on Oral Osseointegration of Titanium Implants: A Biocompatibility Study in Multiple Rat Demographics

Abstract: Dicationic imidazolium-based ionic liquids with amino acid anions, such as IonL-phenylalanine (IonL-Phe), have been proposed as a multifunctional coating for titanium (Ti) dental implants. However, there has been no evaluation of the biocompatibility of these Ti coatings in the oral environment. This study aims to evaluate the effects of IonL-Phe on early healing and osseointegration of Ti in multiple rat demographics. IonL-Phe-coated and uncoated Ti screws were implanted into four demographic groups of rats t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…More cations were observed on the surface due to the net negative charge of the protein (Figure d and e); in particular, more cations are found around the acidic C-terminal tail (see Figure b,c). Figures f,g shows that more anions form hydrogen bonds with the protein compared to cations . From MD contact frequency calculations, it was observed that the atoms of the carboxyl groups of Glu and Asp protein residues are more prevalent around the aromatic regions of the IonL cation (Figure S10–S14).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…More cations were observed on the surface due to the net negative charge of the protein (Figure d and e); in particular, more cations are found around the acidic C-terminal tail (see Figure b,c). Figures f,g shows that more anions form hydrogen bonds with the protein compared to cations . From MD contact frequency calculations, it was observed that the atoms of the carboxyl groups of Glu and Asp protein residues are more prevalent around the aromatic regions of the IonL cation (Figure S10–S14).…”
Section: Resultsmentioning
confidence: 97%
“…Fluids present in biological environments could potentially dissolve an implant coating prior to any beneficial outcomes toward healing. Based on the stability of IonL-coated Ti in a previous subcutaneous rat model study, 72 we can predict that the coating will be temporarily present during the acute inflammatory response that lead to healing. Although previous studies have demonstrated both the biocompatibility and stability of IonL-Phe and IonL-Met in Lewis rats, 72 there have not been any previous studies using IonL as an anchoring thin film for HMGB1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptide coatings have been used to functionalize surfaces and harness the immune system . Thus, a well-characterized, multifunctional IonL ,,, , was used as a method to immobilize key immunomodulatory proteins, such as HMGB1, which was previously studied in vitro and in silico by our group. , However, the behavior of this coating after in vivo implantation is still not well known.…”
Section: Discussionmentioning
confidence: 99%